Numerical Investigation of Unsteady Cavitation Flow around E779A Propeller in a Nonuniform Wake with an Insight on How Cavitation Influences Vortex - Chengzao Han; Yun Long; Xiaorui Bai; Bin Ji (Shock and Vibration)
In the current study, the turbulent cavitation flow around a marine propeller in a nonuniform wake is simulated with the shear stress transport (k−ω SST) turbulence model combining Zwart–Gerber–Belamri (ZGB) cavitation model. The predicted cavity evolution shows a fairly well agreement with the available experimental results. Important mechanisms of propeller cavitation flow, including side-entrant jet and cavitation-vortex interaction, are analyzed in this paper. Vorticity is found to be mainly located in cavitation regions and the propeller wake during propeller rotating. The unsteady behavior of cavitation and side-entrant jet can both promote local vorticity generation and flow unsteadiness. In addition, it is indicated with the relative vorticity transport equation that the stretching term plays a major role in vorticity transportation, while baroclinic torque and Coriolis force term mainly influence the vorticity distribution along the liquid-vapor interface.